PENINGKATAN PENGETAHUAN TENTANG MPASI DAN PICKY EATER PADA IBU BAYI DAN BALITA DI DESA MADEGONDO - Yuniars Renowening; Mohammad Zainul Ma’arif (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2023)
Toddlers are often faced with eating disorders such as picky eaters. A picky eater is a condition where children like to be picky and less responsive to food. This condition will have adverse nutritional impacts in the future, such as growth disorders, developmental disorders, and metabolic disorders. One of the factors that cause picky eaters is giving complementary foods too early and also not in accordance with the principles of balanced nutrition. The community service method is carried out using counseling about giving good and correct complementary foods as well as tips for dealing with children who have picky eating disorders. This activity aims to make mothers of infants and toddlers knowledgeable and also aware of the nutrition for their children. This activity received a good response from the midwife, integrated service post (posyandu) cadres, and also mothers of infants and toddlers, as evidenced by the many questions and discussions.